1996
DOI: 10.1007/bf02245620
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine versus typical antipsychotics a retro- and prospective study of extrapyramidal side effects

Abstract: Schizophrenic patients in long-term neuroleptic monotherapy with clozapine (n = 100) and perphenazine, flupenthixol or zuclopentixol (controls, n = 100) were evaluated for extrapyramidal side effects (EPS) (blind) as well as other side effects and mental condition (non-blind). In both groups the patients had received neuroleptic treatment for a total of 14 years (median) and the present antipsychotic (clozapine or control drug) for 5 years. Thus the clozapine-treated patients had previously received traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 25 publications
1
26
0
3
Order By: Relevance
“…In a study similar to ours, it has also been reported that clozapine had very positive clinical effects during five-year period 22 . our results, concerning the safety profile of clozapine, are in agreement with other studies within ambulatory, long-term setting 23 . Neither the cases of significant blood disorders nor the cases of muscle damage were detected in our patients.…”
Section: Discussionsupporting
confidence: 93%
“…In a study similar to ours, it has also been reported that clozapine had very positive clinical effects during five-year period 22 . our results, concerning the safety profile of clozapine, are in agreement with other studies within ambulatory, long-term setting 23 . Neither the cases of significant blood disorders nor the cases of muscle damage were detected in our patients.…”
Section: Discussionsupporting
confidence: 93%
“…[57][58][59]64 24% of the patients treated with clozapine and 45% of the patients treated with fi rst-generation antipsychotics present with one or more sexual side effects, including erectile and ejaculatory dysfunction. 65 Studies have shown different results: Knegtering et al 57 found olanzapine-induced sexual dysfunction in 27% of their schizophrenic patients; Montejo et al 59 found it in 10-33%; and Bobes et al found Randomized, double-blind, placebo-controlled crossover study 25 Not effective in improving any domain of sexual functioning despite a signifi cant decrease in prolactin levels …”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out, though, that in all of these studies the prevalence and incidence of EPS with clozapine, while low, was not zero. This has also been confirmed in a careful retro-and prospective study of EPS in patients on clozapine versus typical neuroleptics (Gerlach et al 1996). Whether this low incidence represents the lingering effect of previous treatment or is significantly above placebo rates is not clear.…”
Section: Epsmentioning
confidence: 85%